2016
DOI: 10.1080/17425255.2017.1251903
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic properties and drug interactions of apigenin, a natural flavone

Abstract: Apigenin, a natural flavone, is widely distributed in plants such as celery, parsley and chamomile. It is present principally as glycosylated in nature. Higher intake of apigenin could reduce the risk of chronic diseases. It has gained particular interest in recent years as a beneficial, health-promoting agent with low intrinsic toxicity. Areas covered: This review summarizes and the absorption, distribution, metabolism and excretion (ADME) properties of apigenin, and drug-drug interaction of apigenin. Expert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
133
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(136 citation statements)
references
References 96 publications
2
133
0
1
Order By: Relevance
“…The T max of apigenin (measured as aglycone after enzymatic hydrolysis) has been reported to be around 7 h after consumption of parsley [45]. The few human feeding studies involving flavones available so far reported a low bioavailability for this phytochemical [18,46], which could be ascribable to the low absorption of flavones, as demonstrated in the present investigation. Conversely, several scientific data are available for naringenin and hesperetin absorption, and all studies agree about the importance of colonic microbiota activity on this class of (poly)phenols [47,48,49].…”
Section: Discussionsupporting
confidence: 69%
“…The T max of apigenin (measured as aglycone after enzymatic hydrolysis) has been reported to be around 7 h after consumption of parsley [45]. The few human feeding studies involving flavones available so far reported a low bioavailability for this phytochemical [18,46], which could be ascribable to the low absorption of flavones, as demonstrated in the present investigation. Conversely, several scientific data are available for naringenin and hesperetin absorption, and all studies agree about the importance of colonic microbiota activity on this class of (poly)phenols [47,48,49].…”
Section: Discussionsupporting
confidence: 69%
“…Oral bioavailability of apigenin is relatively low due to its poor solubility and because the main part of the ingested apigenin is either excreted unabsorbed or is rapidly metabolized after absorption. In vivo, after ingestion, apigenin is subjected to sulfation and glucuronidation, the absorbed apigenin being present in tissues (mainly hepatic and small intestin) as glucuronide, sulfate conjugates or luteolin [182].…”
Section: Flavonesmentioning
confidence: 99%
“…Apigenin (APG) with three hydroxyl groups in positions 5, 7 and 4 ′ (Figure ) is mainly found in dried flowers of chamomile, parsley, celery, thyme, oregano, olives, onions, kumquats, cherries, oranges, broccoli, tomatoes, barley, carrots, and legumes . In recent years, a lot of research showed that APG have different pharmacological activities, such as anti‐oxidant, anti‐inflammatory, anti‐depressant, anti‐mutagenic, anti‐cancer, anti‐viral, anti‐bacterial, anti‐thrombotic, cardioprotective, hepatoprotective, and immunostimulant effects . The antioxidant activity of APG was previously reported using DFT method .…”
Section: Introductionmentioning
confidence: 99%